"Greeks" in the Neo-Assyrian Levant and "Assyria" in Early Greek Writers - Helm, Peyton Randolph
PhD Diss.; Supervisor: J. D. Muhly; Order No. 8018554; ’Ασσυρίη; jaman, jamnāja; cf. DissAbstr 41 (1980) 1168-A.